Governance windscanner.PT national research infrastructure (PINFRA/22207/2016) - Grosso, José (2022)
This document presents the governance structure foreseen for the operationalization of the WindScanner.PT research infrastructure. The methodology for the implementation of the governance structure, followed the one developed for the European Infrastructure WindScanner.EU, which was the origin of this Portuguese RI. However, as the European RI did not move forward due to a series of situations related to the infrastructure financing rules of the various members of the European consortium. In this sense the Portuguese consortium decided to maintain the project and adapt the RI structure to the Portuguese context and follow a simple model based on the usual research projects, and based on the governance structure defined for WindScanner.EU.